Why are physicians not persuaded by scientific evidence? A grounded theory interview study - Ishizaki Tatsuro; Kitano Nobuko; Imanaka Yuichi; Sekimoto Miho; Takahashi Osamu (BMC, 2006)
Abstract Background The government-led "evidence-based guidelines for cataract treatment" labelled pirenoxine and glutathione eye drops, which have been regarded as the standard care for cataracts in Japan, as lacking evidence of effectiveness, causing great upset among ophthalmologists and professional ophthalmology societies. This study investigated the reasons why such "scientific evidence of treatment effectiveness" is not easily accepted by physicians, and thus, why they do not change their clinical practices to reflect such evidence. Methods We conducted a qualitative study based on grounded theory to explore physicians' awareness of "scientific evidence" and evidence-supported treatment in relation to pirenoxine and glutathione eye drops, and to identify current barriers to the implementation of evidence-based policies in clinical practice. Interviews were conducted with 35 ophthalmologists and 3 general practitioners on their prescribing behaviours, perceptions of eye drop effectiveness, attitudes toward the eye drop guideline recommendations, and their perceptions of "scientific evidence." Results Although few physicians believed that eye drops are remarkably effective, the majority of participants reported that they prescribed eye drops to patients who asked for them, and that such patients accounted for a considerable proportion of those with cataracts. Physicians seldom attempted to explain to patients the limitations of effectiveness or to encourage them to stop taking the eye drops. Physicians also acknowledged the benefits of prescribing such drugs, which ultimately outweighed any uncertainty of their effectiveness. These benefits included economic incentives and a desire to be appreciated by patients. Changes in clinical practice were considered to bring little benefit to physicians or patients. Government approval, rarity of side effects, and low cost of the drops also encouraged prescription. Conclusion Physicians occasionally provide treatment without expecting remarkable therapeutic effectiveness, as exemplified by the use of eye drops. This finding highlights that scientific evidence alone cannot easily change physicians' clinical practices, unless evidence-based practices are accepted by the general public and supported by health policy.